2019
DOI: 10.1111/jon.12607
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Wall MRI Added to MR Angiography in the Evaluation of Suspected Vasculopathies

Abstract: METHODS: Ninety-three consecutive subjects with a clinical history of suspected vasculopathy imaged with both VWI and 3D-TOF-MRAs were retrospectively reviewed. The 3D-TOF-MRAs were reviewed by two independent neuroradiologists classifying arterial segments as normal or abnormal based on caliber changes. Following a 2-week wash-out period, the 3D-TOF-MRAs with VWI together were re-evaluated for caliber changes and/or vessel wall enhancement. A third neuroradiologist served as consensus. Significance was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…1). This finding is in line with studies from the general population that have demonstrated superiority of VW-MRI in the detection of nonstenotic ICAD [7,9,10]. As MRA and CTA primarily capture luminal deficits, ICAD may go undetected on these imaging modalities, especially if atherosclerotic vessels have undergone 'positive remodeling' that does not affect the caliber of the vessel.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1). This finding is in line with studies from the general population that have demonstrated superiority of VW-MRI in the detection of nonstenotic ICAD [7,9,10]. As MRA and CTA primarily capture luminal deficits, ICAD may go undetected on these imaging modalities, especially if atherosclerotic vessels have undergone 'positive remodeling' that does not affect the caliber of the vessel.…”
Section: Discussionsupporting
confidence: 86%
“…VW-MRI complements traditional vessel imaging techniques [e.g. computed tomography angiography (CTA), magnetic resonance angiography (MRA)], which may miss nonstenotic intracranial atherosclerotic lesions [7]. In addition, when combined with luminal imaging, VW-MRI may facilitate differentiation of ICAD from other causes of intracranial arterial disease based on enhancement characteristics [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that VW-MR imaging provides supplemental anatomic information to existing lumenbased imaging techniques. 1,2 Yet, the diagnostic utility of VW-MR imaging in the work-up of ischemic stroke still remains investigative, and questions remain about whether it provides diagnostic information that ultimately improves patient outcomes.…”
mentioning
confidence: 99%
“…Stroke mediated through large- and small-vessel inflammatory vasculopathies are reported neurovascular complications of COVID-19 [ 3 , 4 ]. The putative mechanism of COVID-19-associated vasculitis is SARS-CoV-2 endothelial cell tropism leading to either primary virus- or secondary immune-mediated endothelial dysfunction, as opposed to direct central nervous system infection and dissemination [ 7 ]. In keeping with prior reports underpinning this purported mechanism, SARS-CoV-2 RNA was detected in the serum, but not the cerebrospinal fluid of the patient whose case is reported here within [ 8 ].…”
Section: Discussionmentioning
confidence: 99%